1990
DOI: 10.1073/pnas.87.4.1491
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 regulates production of acute-phase proteins.

Abstract: We explored the possible role of transforming growth factor .I1 (TGF-fi), a cytokine that appears to be an TGF-,8 had no effect on haptoglobin or a,-acid glycoprotein secretion, either directly or in the presence of interleukin 6, which is capable of inducing these proteins. These studies demonstrate that TGF-fi can affect hepatic synthesis and secretion of a subset of acute-phase proteins, both directly and by modulating the effect of interleukin 6. The affected group of plasma proteins is distinct from those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 43 publications
3
47
1
2
Order By: Relevance
“…1,2 However, the level of expression and cytokine regulation of individual APPs appears also to be additionally modulated by the action of endocrine hormones 3,4 and growth factors. [5][6][7] Few studies indicated a modest inhibitory effect of epidermal growth factor (EGF) on APPs in cultured hepatic cells. 8,9 However, EGF action on liver cells, in the context of inflammatory mediators as predicted to be present during acute phase response in vivo, during liver regeneration after partial hepatectomy, or during intrahepatic inflammation, [10][11][12] has not been determined.…”
mentioning
confidence: 99%
“…1,2 However, the level of expression and cytokine regulation of individual APPs appears also to be additionally modulated by the action of endocrine hormones 3,4 and growth factors. [5][6][7] Few studies indicated a modest inhibitory effect of epidermal growth factor (EGF) on APPs in cultured hepatic cells. 8,9 However, EGF action on liver cells, in the context of inflammatory mediators as predicted to be present during acute phase response in vivo, during liver regeneration after partial hepatectomy, or during intrahepatic inflammation, [10][11][12] has not been determined.…”
mentioning
confidence: 99%
“…These include interleukin-1 (IL-1) (8,40,49), interleukin-6 (IL-6) (18, 40), tumor necrosis factor (8, 38, 49), transforming growth factor P, (32), and hepatocyte-stimulating factors I to III (4). No single cytokine, however, has yet been shown to induce the increased synthesis of the full spectrum of acute-phase * Corresponding author.…”
mentioning
confidence: 99%
“…Of course, complement activation also depends on other signals of the immune system like interleukins. Vaccinations are known to affect the acute phase response through cytokines like IL1, IL6 and TGFB1 that are released during the immune response and in particular trigger the expression of C3 (Castell et al 1989;Mackiewicz et al 1990;Gonzalez-Ramon et al 2000). Unlike other complement components with specific functions, C6-9 assembly has the same function in cell lysis because they are all members of the MAC macromolecule.…”
Section: Associationmentioning
confidence: 99%